Student Leadership Development as a new trend of Higher Education in Kazakhstan - Pshembayev, M.A.; Kudysheva, A.A. (KU publ., 2020)
In this paper, some specific issues of student leadership development in Kazakhstan universities were considered. The authors draw attention to the fact that leadership development is now becoming an integral part of the undergraduate and graduate educational programs. This paper reviews different leadership approaches and theories to analyze the question of student leadership development and gives the historical classification of leadership studies in the USA. Likewise, in the paper, a brief review was given to the experience of Toraighyrov University in implementing a specific leadership development program, which is designed with taking into account the cultural, professional and educational uniqueness of the region. The researchers of the article offer another alternative way for leadership skills development — creation of a leadership school in the form of non-government organization. Based on the theoretical research conducted by the authors, the main ways of formation of leadership qualities and necessary skills due to several objective and subjective circumstances were identified.
Студенттік көшбасшылықты дамыту Қазақстанның жоғары білім берудегі жаңа үрдісі ретінде
Развитие студенческого лидерства как новая тенденция в высшем образовании Казахстана
Keywords: leadership; student; leadership development programs; leadership qualities; higher education; leadership theories; Toraighyrov University; Kazakhstan Republic